Methicillin-resistant staphylococcus aureus st9 in pigs in thailand - Jesper Larsen (2018)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an important nosocomial and community-associated pathogen. Recently, livestock-associated MRSA (LA-MRSA) has emerged and disseminated in Europe and North America and now constitutes a considerable zoonotic burden in humans with risk factors of pig exposure, whereas the extent of the livestock reservoir is relatively unknown on other continents. Methodology/Principal Findings: From March through April 2011, MRSA was identified in pigs from 3 out of 30 production holdings in Chang Mai Province, Thailand. Representative isolates were subjected to molecular characterization and antimicrobial susceptibility testing; all isolates had genotypic and phenotypic characteristics of LA-MRSA previously characterized in the region: they belonged to ST9, lacked the lukF-lukS genes encoding Panton-Valentine leukocidin, and were resistant to multiple non-β-lactam antimicrobials. However, unlike other Asian LA-MRSA-ST9 variants, they were spa type t337 and harbored a different staphylococcal cassette chromosome mec IX. Conclusions/Significance: A novel MRSA-ST9 lineage has been established in the pig population of Thailand, which differs substantially from LA-MRSA lineages found in other areas of the continent. The emergence of novel LA-MRSA lineages in the animal agriculture setting is worrisome and poses a serious threat to global public health. © 2012 Larsen et al.